Hierarchical Task Analysis dalam pengembangan gagasan produk - Winta Adhitia Guspara; Winta Tridhatu Satwikasanti; Laode Jiyan (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2018)
Human, have been claimed to be central in a world perspective and bring an another investigating in design science. One of the process development in the design process is using Hierarchy Task Analysis (HTA) for idea development through task analysis. This method constituted from interdisciplinary science between industrial design and ergonomic. In the process, HTA has been adjusted and developed for the design process requirement. This condition affects the process analysis and format of the HTA. The paradigm shift, give more access for a designer to addresses idea development. Furthermore, Human activities, how they do it, using what and what kind of problems that can happen is going focused on user interaction with the product. All of these analysis and idea development is conducted using scheme and sketches. The result of ideas sketches to be able to work on next step process, for example, work on paper models or clay models. The result of ideas sketches to be able to continue work on next step process, for example, product existing analysis and work on modells. Research and developing HTA method for product design had the use of action research approach. This process engages lecturer and student as a user of HTA method. Through this approach, be able to found appropriateness HTA method which solves provided a problem. The result of HTA development has a benefit for a student as a one of planning and product development to arise a product based on ergonomic. Key words: product design, Hierarchy Task Analysis (HTA), ideation, design process, ideas sketches